Eksistensi Hakim dalam Pemikiran Yuridis dan Keadilan - Rusli Muhammad (Jurnal Hukum IUS QUIA IUSTUM, 2014)
The researched problem is how the existence of court judge seen from juridical thinking and justice concept through time is. The research method was normative research with philosophical and conceptual approach. The findings of this research are: first, judges are responsible for judicial proceedings and decision related to all the cases they handle, by using legal logic and thinking as well as justice principles. Second, judges who act as a part of law enforcement are responsible for upholding justice by finding the legal principles by digging, obeying, and understanding any values existing in societies. Third, judges should always make judiciary as a primary institution which is independent and decisive, and as a central institution, not as a marginal institution which is dependent and controlled by any political, financial, and authority influences. Fourth, in the future, judges must be willing to participate actively in eradicating and preventing any occurrence of judicial mafia and making the judiciary free from any judicial mafia. Fifth, maintaining the existence of judges is determined by work performance, professionalism, idealism, and sufficient facility as well as internal and external supports.